Lead-Free Piezoelectrics. - Priya, Shashank; Nahm, Sahn. (New York, NY : Springer, 2011)
Covering a key contemporary issue in the piezoelectrics ceramics industry, this volume is a comprehensive overview of current research into materials and products that contain alternatives to lead, the use of which is becoming ever more restricted.
13.2.4 TS1-Mode Vibration of Oriented BLSF Ceramics.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Piezoelectric ceramics; Electronic books